Retrospective observational studies: Lights and shadows for medical writers - De Sanctis, Vincenzo; Soliman, Ashraf T; Daar, Shahina; Tzoulis, Ploutarchos; Fiscina, Bernadette; Kattamis, Christos; International Network of Clinicians for Endocrinopathies in Thalassemia; Adolescence Medicine (ICET-A) (Acta Biomedica Atenei Parmensis, 2022)
A retrospective study (by definition non-interventional) is a purely observational review and/or reassessment of database records with the aim of analyzing previous events of interest. The ethical and scientific standards for conducting biomedical research with humans have been established in international guidelines. Nevertheless, the reporting of ethical considerations in human research is not yet agreed upon globally, although some progress has been made in recent years. If a study has been granted exemption from ethics approval, this should be indicated in the manuscript (including the reasons for the exemption) and, if formal review by an ethics committee is not available, a statement should be included indicating that the research was conducted according to the principles of the Declaration of Helsinki. Editors play an important role in adherence to these ethical requirements for all submitted and published research papers in their journals. This short review paper focuses on the main lights and shadows of ethical aspects for conducting retrospective observational studies in humans and implications for medical writers.